1999
DOI: 10.4269/ajtmh.1999.61.725
|View full text |Cite
|
Sign up to set email alerts
|

Common occurrence of concurrent infections by multiple dengue virus serotypes.

Abstract: Abstract. The co-circulation of all 4 dengue virus serotypes in the same community, common since the 1950s in Southeast Asia, has now become a frequent occurrence in many Caribbean Islands, Mexico, and Central and South America in the past 20 years. As a consequence, the frequency of concurrent infections would be expected to increase in these areas. To assess this, using state of the art technology, we screened viremic serum samples and mosquitoes inoculated with serum samples collected during epidemics invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(112 citation statements)
references
References 23 publications
8
98
2
1
Order By: Relevance
“…Another important findings of this study was that people exposed to DENV had a significantly higher SGEIgG antibody concentration. These results support the assumption that the risk of virus transmission increases in DENV-endemic areas where people may be exposed to several DENV serotypes in a single infection (29,30). A recent retrospective study showed that the IgG response to the Ae.…”
Section: Discussionsupporting
confidence: 75%
“…Another important findings of this study was that people exposed to DENV had a significantly higher SGEIgG antibody concentration. These results support the assumption that the risk of virus transmission increases in DENV-endemic areas where people may be exposed to several DENV serotypes in a single infection (29,30). A recent retrospective study showed that the IgG response to the Ae.…”
Section: Discussionsupporting
confidence: 75%
“…Cocirculation of multiple DENV serotypes would result in an increased risk of concurrent infections. There is, however, limited documentation describing concurrent infections with more than one serotype in the same individual [13,14]. Furthermore, as already alluded to, sequential infection with more than one [15].…”
Section: Comparison Of the Significant Differences In Clinical Presenmentioning
confidence: 99%
“…All the patients survived during 2005, but 4.55%, 25%, and 2.7% of patients died during 2006-2008. Therefore, the highest mortality rate (25%) occurred during 2007, when 25% of patients had Hb levels < 5g/dL, and 50% had severe thrombocytopenia (11)(12)(13)(14)(15)(16)(17)(18)(19)(20),000 platelets/μL). Consequently, 25% of patients required blood and platelet transfusions.…”
Section: Comparison Of the Significant Differences In Clinical Presenmentioning
confidence: 99%
“…Concurrent multiserotype infections by DENV have been described in several dengue-prevalent countries [7,8,10,[15][16][17]. The proportion of such patients could be as high as 5%-15% [16,17], and the number of serotypes as many as 3 [7,8,15].…”
Section: Discussionmentioning
confidence: 99%